Ketofast : rejuvenate your health with a step-by-step guide to timing your ketogenic meals - Mercola, Joseph (Hay House, Inc., 2019)
We all know that food is medicine--yet going without food is one of the single best things you can do for your health. Short, doable fasts, when strategically timed, are an incredibly powerful metabolic intervention, dovetailing perfectly with a ketogenic diet to activate your body's fat-burning mode. This in turn can ward off insulin resistance, reduce oxidative stress and inflammation, optimize brain function, prevent neurological problems, support weight loss, and more. In this in-depth yet accessible guide, Dr. Joseph Mercola explores the profound health benefits that result when ketogenic living and well-planned fasting are combined. Topics include: * How our food is making us sick and what we can do about it * The physiology and mechanisms of fasting, including stem cell activation * How the cyclical ketogenic diet--with fasting included--differs from the conventional keto diet * How fasting works and how safe it is for you * How regular one-day fasts support fat burning and detoxification while minimizing hunger and side effects * How to monitor your progress with lab tests * And much more.